Ten years of gas shale fracturing in China: Review and prospect - Jinzhou Zhao; Lan Ren; Tingxue Jiang; Dongfeng Hu; Leize Wu; Jianfa Wu; Congbin Yin; Yongming Li; Yongquan Hu; Ran Lin; Xiaogang Li; Yu Peng; et al. (Natural Gas Industry B, 2022)
The first fractured shale gas well of China was constructed in 2010. After 10 years of development, China has become the second country that possesses the core technology of shale gas development around the world, realized the shale gas fracturing techniques from zero to one and from lagging to partially leading, and constructed the fracturing theory and technology system suitable for middle–shallow marine shale gas exploitation. In order to provide beneficial guidance for the efficient exploitation of shale gas in China in the future, this paper comprehensively reviews development history and status of domestic fundamental theories, optimized design methods, fluid systems, tools and technologies of shale gas fracturing and summarizes the research results in fundamental theories and optimized design methods, such as fracturing sweet-spot cognition, fracture network propagation simulation and control, rock hydration and flowback control, and SRV (stimulated reservoir volume) evaluation and characterization. The development and application of slick-water fracturing fluid system and new fracturing fluid with little or no water is discussed. The development and independent research & development level of multi-stage fracturing tools are evaluated, including drillable composite plug, soluble plug, large-diameter plug and casing cementing sleeve. The implementation situations of field technologies and processes are illustrated, including the early conventional multi-stage multi-cluster fracturing and the current “dense cluster” fracturing and temporary plugging fracturing. Based on this, the current challenges to domestic shale gas fracturing technologies are analyzed systematically, and the development direction of related technologies is forecast. In conclusion, it is necessary for China to continuously research the fracturing theories, technologies and methods suitable for domestic deep and ultra-deep marine shale gas, terrestrial shale gas and transitional shale gas to facilitate the future efficient development of shale gas in China.